DIAGNOSTICS OF SOCIAL ACTIVITY OF FUTURE SOCIAL WORKERS - Soroka, Olga (Social work and education, 2018)
It is analyzed in the article the general approaches to the problem of social activity of the individual. During research it is presented the various scientific approaches to the essence of the concept of “social activity”. That is a systemic social quality, a general characteristic of the individual, a complex structure. It is specified the term “social activity of future social workers”. It is understood as the integrative quality of the individual, based on the system of value orientations, target objects and manifested in an active life position. It is the desire to influence social processes in society. The activity is realized in a purposeful, conscious, socially meaningful activity. It is established that social activity is revealed in the system of needs, motives, guides, interests, which determine the implementation of certain actions. There are presented the substantive characteristics of social activity of students – future social workers. The complex of motives of activity, personality characteristics and appropriate skills. The purpose of scientific work is to present the results of an empirical study. The study is based on the diagnosis of social activity of students of ІI-IV courses – future social workers of Ternopil National Volodymyr Hnatyuk Pedagogical University.Diagnostics of social activity was carried out with the help of a set of techniques: the methodology of E. Stepanov for determining the level of social activity, L. Baiborodova methodology for determining the students’ motives regarding their participation in student self-government activities; M. Rozhkov methods for determining the level of social adaptability, activity, autonomy and moral education. The results of the diagnosis showed the predominance of students of forced and active-executive activity. It also showed the collectivist and personal motives, the average level of social activity and adaptability, and humanistic values.